2010
DOI: 10.4171/ggd/102
|View full text |Cite
|
Sign up to set email alerts
|

Largeness of LERF and 1-relator groups

Abstract: Abstract. We consider largeness of groups given by a presentation of deficiency 1, where the group is respectively free-by-cyclic, LERF or 1-relator. We give the first examples of (finitely generated free)-by-Z word hyperbolic groups which are large, show that a LERF deficiency 1 group with first Betti number at least two is large or Z Z and show that 2-generator 1-relator groups where the relator has height 1 obey the dichotomy that either the group is large or all its finite images are metacyclic. Mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…. As pointed out in [5], the argument of [14, Proposition 2.1 and Theorem 2.2] then shows that G 2 (w) is large.…”
Section: The Alexander Polynomialmentioning
confidence: 86%
See 1 more Smart Citation
“…. As pointed out in [5], the argument of [14, Proposition 2.1 and Theorem 2.2] then shows that G 2 (w) is large.…”
Section: The Alexander Polynomialmentioning
confidence: 86%
“…More generally, one can ask how common it is for a two-generator one-relator group to be large or to have virtual first Betti number greater than one. Button has used the Alexander polynomial to study large one-relator groups [5,6]. In particular, he has shown that the vast majority of two-generator one-relator presentations in 'Magnus form' with cyclically reduced relation of length at most 12 are large (see [6,Theorem 3.3]).…”
Section: Furthermore If W Is Not a Proper Power Then ψ Is An Isomorpmentioning
confidence: 99%
“…Definition 3.11 ('angle and swap'). By (10) and (11) j} ( a s )). Now, we can use the injectivity of the homomorphism ν {i,j} : G {i,j} → G to conclude that a s = ϕ {i}{i,j} ( a s ).…”
Section: (9) If a Bridge Of Type I Is Incident With A Local Vertex Ofmentioning
confidence: 99%
“…Definition 3.11 ('angle and swap'). By (10) and (11), we know that every local vertex D k is of some type {i, j} with distinct i, j ∈ I. By (9), such a local vertex is incident with bridges each of which is either of type i or of type j.…”
Section: Statement and Proof Of The Intersection Theoremmentioning
confidence: 99%
“…Thus on regarding "well behaved geometrically" to mean CAT(0) and "well behaved group theoretically" to mean residually finite, we have 1-relator groups R p,p which are well behaved group theoretically but not geometrically, 1-relator groups R p,3p which are well behaved geometrically but not group theoretically, and (for p > 3) 1relator groups R p,p−1 which are neither, all without unbalanced Baumslag -Solitar subgroups. This construction also allows us to answer Question 20 in [7], namely (for p even) the 2-generator 1-relator group R p,p/2 is residually finite but has no finite index subgroup which is an ascending HNN extension of a finitely generated free group.…”
Section: Introductionmentioning
confidence: 99%